Pengaruh Proses Pengolahan terhadap Kadar Pati Resisten Sukun (Artocarpus altilis Park) - STP, MP, Rosida; Yulistyani, Ratna (UPN VETERAN JAWA TIMUR, 2011)
A study on the effect of processing on resistant starch (RS) content of Breadfruit (Artocarpus altilis Park) has been conducted. The aim of this research was to evaluate a resistant starch formation in pre-cooked flour made of breadfruit using different processing methods. The principle of preparing the pre-cooked flour is improving retrograded starch content which is a kind of resistant starch (type 3) The processing included boiling, steaming, and frying, and each processing was combined with cooling for 24 hours in refrigerator, prior to drying, milling and shieving. It was found that processing (combination of heating and cooling)increased Resistant Starch (RS) content of breadfruit. Boiling and cooling changed RS from 3.27%to 3.82% (16.8%), steaming and cooling changed RS from 3.27% to 6.67% (103.9%) and frying and cooling changed RS from 3.27% to 3.68% (12.5%). Pre-cooked flour from the best treatment (steaming and cooling) was tried to be applied in making of biscuit, cakes and sweet bread (with various formulation). The products prepared by substitution with pre-cooked flour (until 30%) were preferred by the panels in term of color, taste and texture and they have medium resistant starch content (2,5-5,0%), so that they can be developed as the kind of functional food.Key words : breadfruit, processing method, pre-cooked flour, resistant starch(RS), functional food